A Conservation Difference Scheme of Generalized Boussinesq Equation - Xiaoli Jiang; Xiaofeng Wang (Discrete Dynamics in Nature and Society)
We focus on the algorithm research of a class of six-order generalized Boussinesq equation. We use the finite difference method to discrete the Boussinesq equation. The discrete format with the law of energy conservation is deduced; stability and existence and good order of convergence properties are also derived. The efficiency of the proposed method is tested to numerical results that the convergence of space is of second-order and the conservation law of energy is verified very well for the energy difference.